Mind the gap between policy imperatives and service provision: a qualitative study of the process of respiratory service development in England and Wales - Sheikh Aziz; Kielmann Tara; Powell Alison; Tierney Alison; Huby Guro; Hamilton Sonya; Pinnock Hilary (BMC, 2008)
Abstract Background Healthcare systems globally are reconfiguring to address the needs of people with long-term conditions such as respiratory disease. Primary Care Organisations (PCOs) in England and Wales are charged with the task of developing cost-effective patient-centred local models of care. We aimed to investigate how PCOs in England and Wales are reconfiguring their workforce to develop respiratory services, and the background factors influencing service redesign. Methods Semi-structured qualitative telephone interviews with the person(s) responsible for driving respiratory service reconfiguration in a purposive sample of 30 PCOs. Interviews were recorded, transcribed, coded and thematically analysed. Results We interviewed representatives of 30 PCOs with diverse demographic profiles planning a range of models of care. Although the primary driver was consistently identified as the need to respond to a central policy to shift the delivery of care for people with long-term conditions into the community whilst achieving financial balance, the design and implementation of services were subject to a broad range of local, and at times serendipitous, influences. The focus was almost exclusively on the complex needs of patients at the top of the long-term conditions (LTC) pyramid, with the aim of reducing admissions. Whilst some PCOs seemed able to develop innovative care despite uncertainty and financial restrictions, most highlighted many barriers to progress, describing initiatives suddenly shelved for lack of money, progress impeded by reluctant clinicians, plans thwarted by conflicting policies and a PCO workforce demoralised by job insecurity. Conclusion For many of our interviewees there was a large gap between central policy rhetoric driving workforce change, and the practical reality of implementing change within PCOs when faced with the challenges of limited resources, diverse professional attitudes and an uncertain organisational context. Research should concentrate on understanding these complex dynamics in order to inform the policymakers, commissioners, health service managers and professionals.